The Importance Of The Maple System In The Development Of Professional Competence Of Students Of Technical Higher Education Institutions - Usmanov Akram Ahmadjanovich; Fayzullaev Jamshid Ismoiljonovich; Usmonova Marguba Sodiqovna (Genius Journals, 2022)
In this article, the purpose of the development of professional competence at the present stage of preparation of students of Technical Higher Education Institutions for professional activity is actively revealed, as well as finding solutions to problems encountered in professional activity is demonstrated through the MAPLE system.
Keywords: science; engineering; students; mathematics